Implementasi Kebijakan Kurikulum Merdeka di Sekolah Dasar: Tantangan dan Peluang - Okki Yansah; Masduki Asbari; Gilang Maulana Jamaludin; Arita Marini; Zulela MS (Journal of Information Systems and Management (JISMA), 2023)
This research was conducted to analyze the implementation of the Merdeka Curriculum at Al-Anshory Boarding Elementary School in Cirebon City using a phenomenological approach. This qualitative study explores the individual experiences of teachers, principals, and supervisors through observation, interviews, and documentary studies. Efforts were made to ensure data validity, including extending the data collection period, conducting continuous observation, triangulation, and involving peers in discussions. The results of the study show that the Merdeka Curriculum in elementary schools can produce students with noble character, independence, critical thinking, creativity, cooperation, and a sense of diversity. The principal encourages various unique and innovative participatory programs. However, the implementation of the Merdeka Curriculum faces challenges such as resource constraints, lack of training, and limited learning time. Nevertheless, there are opportunities to improve implementation through collaboration between teachers, principals, and supervisors involving the community and utilizing technology. This research provides insights to overcome challenges and take advantage of opportunities in implementing the Merdeka Curriculum in elementary schools.